PEMINATAN SISWA KELAS XII SELEPAS LULUS SMA DI SEKOLAH MENENGAH ATAS NEGERI 1 KUOK - Pratiwi, Wella Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study was conducted in SMK 1 Subdistrict Kuok. The aim of this study was to determine the forms of the desired interest and attention in SMAN 1 Kuok. This study entitled "Specialisation Class XII After Graduating Senior in High School State 1 Kuok". Topics focus of this study is what the specialization class XII students after graduating from SMAN 1 Kuok. Informants of this study was students in SMAN 1 Kuok. Informants retrieval is done by using purposive sampling. Informants are numbered 15 students. Writer using qualitative descriptive method and data analyzed qualitative. Data instrument is observation, interview and documentation. The results showed that election interest respondents the most was interest in continuing education or courses totaling 6, followed by interest in the job consists of 4 respondents, anyone has the intention to marry amounted to 2 people and there were 3 respondents who chose to rest or unemployed first. In addition there are several things that affect the interests of students, namely the attention of parents and families as well as those closest to the interest of the respondents, and acts sera response to the interest of the selected respondents.Keywords: Children Interest, Student Options